Houseboat and floating islands in hotel & restaurant business - Volkova, Daria; Tyshchenko (Usatiuk), Olena (My University, 2015)
In this paper we describe the use of floating islands and houseboat in the tourism and especially in hotel & restaurant business. This article shows the designing of different types of sea floating recreations, which was developed in last year’s. All floating and sea innovations can become a new experience for visitors of restaurants and hotels. Attention was focused on two islands and its features that are some of the most luxurious hotels and resorts in the world; and two worlds famous restaurants by its incredible architectural decision.
Keywords: houseboat; плавучий будинок; floating islands; плавучі острови; sea recreation; морський відпочинок; hotel business; готельний бізнес; кафедра технології харчування та ресторанного бізнесу